Hubungan Penggunaan Paylater Terhadap Tingkat Pengeluaran Mahasiswa Generasi Z - Krisnayanti, Indari; Larasati, Larasati; Hidayatullah, M. Rizky; Nurhasidah, Nurhasidah; Jayanti, Wanti Eka J (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The rapid growth of digital financial technology has encouraged the widespread adoption of Buy Now Pay Later (BNPL) services, commonly known as PayLater, particularly among Generation Z university students. This study aims to examine the relationship between the use of PayLater and the level of monthly spending among Generation Z university students. A quantitative correlational approach was applied, with primary data collected through an online questionnaire distributed via Google Form to students who had experience using PayLater services, using a purposive sampling technique. Of the 124 questionnaires collected, 113 were declared valid for analysis after data cleaning. The research instrument, consisting of 20 statement items across both variables, was tested for validity using Pearson Product Moment correlation and for reliability using Cronbach's Alpha, and was found to be valid and highly reliable (Cronbach's Alpha of 0.972 for the PayLater Use variable and 0.966 for the Student Spending Level variable). Classical assumption tests confirmed that the linearity and homoscedasticity assumptions were met, although the normality assumption was not fully satisfied; the analysis was nevertheless considered robust given the sufficiently large sample size (N = 113), in line with the Central Limit Theorem. The Pearson correlation test revealed a very strong, positive, and significant relationship between PayLater use and student spending level (r = 0.889; p < 0.001). Simple linear regression analysis produced the equation Y = 3.538 + 0.885X, with a coefficient of determination (R²) of 0.790, indicating that PayLater use explains 79.0% of the variation in student spending, while the remaining 21.0% is explained by other factors outside the model, such as financial literacy and selfcontrol. These findings confirm that the higher the intensity of PayLater use, the higher the monthly spending reported by Generation Z students, underlining the urgent need for stronger digital financial literacy education among young consumers.